Detection of Bacteria Bearing Resistant Biofilm Forms, by Using the Universal and Specific PCR is Still Unhelpful in the Diagnosis of Periprosthetic Joint Infections - Zegaer, Batool H.; Ioannidis, Anastasios; Babis, George C.; Ioannidou, Vassiliki; Kossyvakis, Athanassios; Bersimis, Sotiris; Papaparaskevas, Joseph; Petinaki, Efthimia; Pliatsika, Paraskevi; Chatzipanagiotou, Stylianos (Frontiers in Medicine, 2014)
Intraoperative conventional bacteriological cultures were compared with different polymerase chain reaction (PCR) methods in patients with total joint arthroplasties. The isolated bacteria were investigated for biofilm formation, and the biofilm forming strains, in their planktonic and biofilm forms, were further tested for their antimicrobial resistance against several clinically important antimicrobials. Forty four bone and joint samples were included and classified as infected or non-infected according to standard criteria for periprosthetic hip and knee infections. For the bacteriological diagnosis, conventional culture, two types of universal PCR and species specific PCR for three selected pathogens (S. aureus, S. epidermidis, P. aeruginosa) were applied. Biofilm formation determination was performed by the tissue culture plate method. Antimicrobial susceptibility of the planktonic bacteria was performed by the minimal inhibitory concentration determination and, of the biofilm forms, by the minimal inhibitory concentration for bacterial regrowth from the biofilm. Twenty samples were culture positive, with S. epidermidis, S. aureus or P. aeruginosa. All PCR methods were very ineffective in detecting only one pathogen. All isolates were biofilm positive and their biofilm forms, were highly resistant. In this study, compared to PCR, culture remains the “gold standard”. The biofilm formation by the causative bacteria and the concomitant manifold increased antimicrobial resistance may explain the clinical failure of treatment in some cases and should be considered in the future for therapeutic planning.